DIGITAL MARKETING STRATEGY: PRIORITY AND BARRIERS FOR SMALL AND MEDIUM INDUSTRIES - Sari Laelatul Qodriah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of this study is to examine digital marketing practices in small and medium industries. The aspects studied include the digital marketing strategies and tactics used, as well as the level of difficulty experienced by small and medium-sized industries when marketing digitally. Respondents in this study were managers or business owners in small and medium industries in Indonesia. This study uses a quantitative descriptive method. The findings in this study indicate that the components of the digital marketing strategy are considered very important or are priority strategies used by small and medium industries, but on the other hand the seven this strategy has a high difficulty for small and medium industries to achieve success in carrying out the strategy. The component of digital marketing tactics are considered very effective in promoting their products, but small and medium industry players have difficulties to apply these tactics.